The Host Shapes the Gut Microbiota via Fecal MicroRNA - Liu, Shirong; da Cunha, Andre Pires; Rezende, Rafael M; Cialic, Ron; Wei, Zhiyun; Bry, Lynn; Comstock, Laurie E; Gandhi, Roopali; Weiner, Howard L (Cell host & microbe, 2016)
The host gut microbiota varies across species and individuals but is relatively stable over time within an individual. How the host selectively shapes the microbiota is largely unclear. Here, we show that fecal microRNA (miRNA)-mediated inter-species gene regulation facilitates host control of the gut microbiota. miRNAs are abundant in mouse and human fecal samples and present within extracellular vesicles. Cell-specific loss of the miRNA-processing enzyme, Dicer, identified intestinal epithelial cells (IEC) and Hopx-positive cells as predominant fecal miRNA sources. These miRNAs can enter bacteria, such as F. nucleatum and E. coli, specifically regulate bacterial gene transcripts, and affect bacterial growth. IEC-miRNA-deficient (Dicer1(ΔIEC)) mice exhibit uncontrolled gut microbiota and exacerbated colitis, and WT fecal miRNA transplantation restores fecal microbes and ameliorates colitis. These findings identify both a physiologic role by which fecal miRNA shapes the gut microbiota and a potential strategy for manipulating the microbiome.